Adsorption characteristics of ionic liquid assisted MOFs : zeolite composites and water systems - Tan, Caselyn Jing Wen (Nanyang Technological University, 2020)
Throughout the years, the increasing trend of Global warming is alarming. This poses devastating consequences for planet Earth. The main effect of Global warming is primarily because of the excessive burning of fossil fuels to generate energy to meet the high demand. This produces carbon dioxide (CO2), methane and other greenhouse gases into the atmosphere, which result to gradual heating of the Earth's surface. This issue drives the interest of exploration for various methods that can reduce the energy consumption of systems. One of them is the adsorption assisted system, with is potentially attractive to be an environmentally sustainable alternative replacement for the current compression assisted cooling system. Providing with benefits of enabling low cost production, water assisted adsorption simplifies system control, reduces noise pollution and no coolant pollution as it adopts non-hazardous refrigerant. To increase the efficiency and develop a compact system, the performance of water adsorption process play an important role. This report focuses on the research of water adsorption on modified MOFs (Ionic Liquid/ Zeolite composites). To identify the best combination of MOFs modified by adding ionic liquid and conventional adsorbents that will produce the most effective rate of water adsorption process. The adsorption experiments are conducted for temperatures ranging from 303K to 338K and pressures up to 10kPa. To quantify the performance of the MOF composites, it is determined by obtaining the adsorption isotherms plots and kinetics model from the thermogravimetric analyser that is used to measure the amount of water vapour uptake directly. These results will be converted into an isotherm plot to understand the thermodynamics properties related to the MOF composites interaction with water, and adsorption kinetics data are fitted with Langmuir Kinetics equation to evaluate the time needed for the interaction to achieve the steady-state. Further analysis of the modified MOF-characteristics is conducted which include the adsorbent morphology and thermal stability. The proposed composite adsorbents were successfully synthesized before experimental investigation. The isotherms and kinetics results indicate that MIL-101 (Cr) MOFs with BMIM ionic liquid exhibit the superior adsorption properties in terms of higher water transfer per adsorption-desorption cycle.